In ovo injection effect of sodium nitrite on hatchability, day-old chick quality, organ weights and body antioxidant status of newly hatched chicks - MOHAMADI, ELMIRA; DANESHYAR, MOHSEN; ARDABILI, FARHAD FAROKHI (The Indian Journal of Animal Sciences, 2014)
This experiment was conducted to investigate the effect of sodium nitrite injection per egg on day 7 of incubation on chick quality, hatchability, chick weights and some blood antioxidant metabolites in chicken embryo. Fertile eggs (308) were injected by 4 different levels of 0, 0.042, 0.084 and 0.168 mg per egg sodium nitrite at day 7 of incubation. At hatch, no effect of sodium nitrite injection was indicated on hatchability and mortality, chick quality and organ weights. However chick weight of sodium nitrite injected eggs were lower than those of control chicks. No significant differences were observed between the treatments for activity of blood superoxide dismutase and glutathione peroxidase. Blood malondialdehyde content of chicks from 0.084 mg sodium nitrite injected eggs was greater than control and 0.042 mg sodium nitrite injected ones. Furthermore, lower blood total antioxidant capacity was observed for chicks of 0.042 and 0.168 mg sodium nitrite injected eggs as compared to those of control eggs. It was concluded that In ovo injection of sodium nitrite does not exert negative effects on 1–day chick quality, hatchability and mortality, but it decreased the both chick weights and blood antioxidant status.